Rich dad poor dad for teens : the secrets about money--that you don't learn in school - Kiyosaki, Robert T, 1947- (Rich dad series.)
Summary: An age-appropriate guide encourages the development of confident and responsible money skills, providing case examples, sidebars, and attitude recommendations that demonstrate how to achieve security in today's challenging job market.